Integração lavoura - pecuária - floresta na recuperação de pastagens degradadas no norte de Minas Gerais - Veronica Alves Mota (2009)
Faced of the reality of global agriculture, the need for food production is each time bigger. Thus, the use of chemical inputs and farm machinery on a large scale are increasing, bringing consequences for the Brazilian soils. The North of Minas Gerais, livestock region, fits in this same situation and has areas of degraded pastures by many reasons, including lack of cultural practices. This proposal aims to work with the integration farming livestock forest so that this technology can be further studied and disseminated to all producers in the region. So with the development of experiments, will be determined: the interference of sorghum and its production when grown in consortium with other forage species, the effects of intercropping of forage species with sorghum for silage in the formation, establishment and pasture production; the effect of the atrazine herbicide in the production of sorghum for silage in intercropping with forage species; the effect of shading on the forages Andropogon gayanus cv. Planaltina and Panicum maximum cv. Tanzania. The proposal was composed by 3 experiments that were conducted in the dependencies of the Department of Plant Science and Animal Science of the Federal University of Minas Gerais, Montes Claros-MG. About the results related to the first experiment it was found that the production of A. gayanus cv. Planaltina and P. maximum cv. Tanzania is higher in environment shaded than in full sun. A. gayanus cv. Planaltina shows higher production when subjected to the shading of 30% compared to 50% shade, while P. maximum cv. Tanzania has not distinguish between shading levels tested, in relation to the productivity of forage. Shade plants of A. gayanus cv. Planaltina and P. maximum cv. Tanzania have physiological changes in leaves, with increases in levels of chlorophyll a. The time of entry into the shade does not change the productivity and leaf chlorophyll content of A. gayanus cv. Planaltina and P. maximum cv. Tanzania. The bromatological composition of A. gayanus cv. Planaltina and P. maximum cv. Tanzania is similar in plants maintained under 30 and 50% of shading and in full sun, whatever the time of entry into the shade.In relation to the experiments with integration Farming-Livestock-Forest, the results were that the main species present in the area were Digitaria horizontalis, Eulesine indica, Sorghum arundinaceum, Cyperus rotundus, Ipomoea sp., Commelina benghalensis, Acacia plumosa, Portulaca oleracea, Amaranthus deflexus, Sida sp. and Richardia brasiliensis. The type of management adopted for weed control with and without the application of atrazine does not affect the production of sorghum, making possible the consortium of that culture when dense with forage in agroecological production systems. The application of atrazine does not change drastically weed communities proved by the high similarity between areas with and without herbicide application and the forages Brachiaria brizantha cv. Xaraés and Panicum maximum cv. Tanzania are productive options for consortium in integration systems Farming-Livestock with the sorghum, being the Panicum maximum cv. Tanzania the one with the greatest dry matter production and the greatest vegetal cover.